Advertisements
Advertisements
Question
Simplify : (4x – 5y) (5x – 4y)
Sum
Solution
(4x – 5y) (5x – 4y)
= 4x(5x – 4y) – 5y(5x – 4y)
= 20x2 – 16xy – 25xy + 20y2
= 20x2 – 41xy + 20y2
shaalaa.com
Multiplying a Polynomial by a Polynomial
Is there an error in this question or solution?
APPEARS IN
RELATED QUESTIONS
Multiply: 2y − 4y3 + 6y5 by y2 + y − 3
Simplify : (7x – 8) (3x + 2)
Simplify: (5a + 5b – c) (2b – 3c)
Find the value of (3x3) × (-5xy2) × (2x2yz3) for x = 1, y = 2 and z = 3.
Evaluate (3x4y2) (2x2y3) for x = 1 and y = 2.
If x = 2 and y = 1; find the value of (−4x2y3) × (−5x2y5).
Evaluate: xy2(x – 5y) + 1 for x = 2 and y = 1.
Multiply and then verify :
−3x2y2 and (x – 2y) for x = 1 and y = 2.
Multiply: 2x2 – 4x + 5 by x2 + 3x – 7
Multiply: (ab – 1) (3 – 2ab)